Implementation Of Information Systems On E-commerce Websites As Media To Deliver Information - Alwiyah, Alwiyah; Greisy, Chloe; Afitri, Afni (Aptisi Transactions On Technopreneurship (ATT), 2019)
Attendance information conducted by students can now be easily accessed by a supervisor. However, there are 3 (three) difficulties faced by supervisors, one of which is presenting information with tables requiring considerable time and very high accuracy to measure the comparison of information contained within it. In order to facilitate the supervisor in recording and measuring attendance of student tutoring students handled, the Attendance Rating system will present information in the form of graphics using Highchart. Presentation of information in the form of a graph on Attendance Assessment will present information in the form of Nim (Student Registration Number), supervisor, and guidance time. Information on the guidance time in the graph can be used as a comparison to measure the level of student activity in following the guidance. The Attendance Rating System uses the YII Frameworkbased website because it is also easy to develop web applications and the YII Framework has a good level of security. In this study, there are 5 (five) advantages and 1 (one) deficiency in the Attendance Assessment system. With this research, it is expected that the Attendance Assessment system can improve the quality of student attendance in the tutoring process at Raharja College.